2005
DOI: 10.1084/jem.20041948
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal antiinflammatory effect of 5-aminosalicylic acid is dependent on peroxisome proliferator–activated receptor-γ

Abstract: 5-aminosalicylic acid (5-ASA) is an antiinflammatory drug widely used in the treatment of inflammatory bowel diseases. It is known to inhibit the production of cytokines and inflammatory mediators, but the mechanism underlying the intestinal effects of 5-ASA remains unknown. Based on the common activities of peroxisome proliferator–activated receptor-γ (PPAR-γ) ligands and 5-ASA, we hypothesized that this nuclear receptor mediates 5-ASA therapeutic action. To test this possibility, colitis was induced in heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
354
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(372 citation statements)
references
References 62 publications
11
354
1
6
Order By: Relevance
“…Several mechanisms of action for 5 ASAs have been proposed, including reduction of prostaglandin synthesis via inhibition of cyclooxygenase, suppression of proinflammatory cytokine production and oxygen free radicals, inhib ition of lipoxygenase, blockade of neutrophil chemo taxis and mast cell activation, and impairment of nuclear factor κB activation (NF κB) in immune cells 3 . Moreover, studies in mice revealed that 5 ASA based drugs augment peroxisome proliferator activated receptor γ (PPARγ) expression and promote PPARγ translocation from the cytoplasm to the nucleus where they result in activation of peroxisome proliferator hormone response element driven genes to suppress colitis activity 6,7 .…”
mentioning
confidence: 99%
“…Several mechanisms of action for 5 ASAs have been proposed, including reduction of prostaglandin synthesis via inhibition of cyclooxygenase, suppression of proinflammatory cytokine production and oxygen free radicals, inhib ition of lipoxygenase, blockade of neutrophil chemo taxis and mast cell activation, and impairment of nuclear factor κB activation (NF κB) in immune cells 3 . Moreover, studies in mice revealed that 5 ASA based drugs augment peroxisome proliferator activated receptor γ (PPARγ) expression and promote PPARγ translocation from the cytoplasm to the nucleus where they result in activation of peroxisome proliferator hormone response element driven genes to suppress colitis activity 6,7 .…”
mentioning
confidence: 99%
“…26 It has recently been clearly established that the epithelial cell is the predominant and possibly only target cell for mesalazine in UC, 27 but the differential effects of systemic and topical corticosteroids suggest that this may not be the principal target for corticosteroids, even when topically administered. The efficacy demonstrated in this study with a corticosteroid that shows minimal systemic effect does, however, suggest that the steroid target cells, at least in patients who do not have severe colitis, are present within the mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…At 6 months, remission rates were 51% for Predocol 40 mg ⁄ day, 38% for Predocol 60 mg ⁄ day and 32% for tapering prednisolone (P = 0.08). [25][26][27]; h tapering prednisolone ⁄ placebo (n = 38-39). P-values reflect the adjusted mean treatment differences using analysis of covariance.…”
Section: Safetymentioning
confidence: 99%
“…13,14 PPAR␥ is a member of the superfamily of nuclear receptors and has important anti-inflammatory activity, 15,16 because it inhibits the activation of nuclear factor B (NF B) and the expression of the proinflammatory cytokines IL-1␤ and tumor necrosis factor-␣ (TNF-␣). [17][18][19] The colon expresses a high density of PPAR␥, 20,21 and much evidence points to the involvement of the PPAR␥ receptor in the regulation of intestinal inflammation.…”
mentioning
confidence: 99%